Psychological insulin resistance in geriatric patients with diabetes mellitus - Bahrmann, Anke; Abel, Amelie; Zeyfang, Andrej; Petrak, Frank; Kubiak, Thomas; Hummel, Jana; Oster, Peter; Bahrmann, Philipp (Patient education and counseling, 2014)
Objective - To determine the extent to which geriatric patients with diabetes mellitus experience psychological insulin resistance (PIR). - Methods - A total of 67 unselected geriatric patients with diabetes (mean age 82.8±6.7 years, diabetes duration 12.2 [0.04-47.2] years, 70.1% female) were recruited in a geriatric care center of a university hospital. A comprehensive geriatric assessment (CGA) was performed including WHO-5, Hospital Anxiety and Depression Scale (HADS), Mini Mental State Examination (MMSE) and Barthel-Index. We assessed PIR using the Barriers of Insulin Treatment Questionnaire (BIT) and the Insulin Treatment Appraisal Scale in a face-to-face interview. - Results - Insulin-naïve patients (INP) showed higher PIR scores than patients already on insulin therapy (BIT-sum score: 4.3±1.4 vs. 3.2±1.0; p<0.001). INP reported in the BIT increased fear of injection and self-testing (2.4±2.4 vs. 1.3±0.8; p=0.016), expect disadvantages from insulin treatment (2.7±1.6 vs. 1.9±1.4; p=0.04), and fear of stigmatization by insulin injection (5.2±2.3 vs. 3.6±2.6; p=0.008). Fear of hypoglycemia, however, did not differ significantly (6.3±2.8 vs. 5.1±3.1; p=0.11). Depression was not shown to be a barrier to insulin therapy. - Conclusion - INP with diabetes have a significantly more negative attitude toward insulin therapy in comparison to patients already on insulin. - Practice implications - Systematic assessment of barriers of insulin therapy, individualized diabetes treatment plans and information of patients may help to overcome such negative attitudes, leading to quicker initiation of therapy, improved adherence to treatment and a better quality of life.
Online 1 December 2013
Gesehen am 21.09.2020